2017
DOI: 10.1186/s12929-017-0394-0
|View full text |Cite
|
Sign up to set email alerts
|

Zinc transporters and insulin resistance: therapeutic implications for type 2 diabetes and metabolic disease

Abstract: BackgroundZinc is a metal ion that is essential for growth and development, immunity, and metabolism, and therefore vital for life. Recent studies have highlighted zinc’s dynamic role as an insulin mimetic and a cellular second messenger that controls many processes associated with insulin signaling and other downstream pathways that are amendable to glycemic control.Main bodyMechanisms that contribute to the decompartmentalization of zinc and dysfunctional zinc transporter mechanisms, including zinc signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 84 publications
(90 reference statements)
2
43
0
Order By: Relevance
“…The Slc39a family was named ZIP (Zrt-, Irt-related protein), after the first two known members Irt1 of Arabidopsis thaliana and Zrt1 of Saccharomyces cerevisiae . So far, the exact structure of mammalian ZIP proteins has not been established, but 14 members of human and mouse ZIP isoforms and their genes have been isolated and characterized [16,17,35]. ZIP family members mediate Zn 2+ influx from the extracellular place into cells, or from the intracellular Zn 2+ store into the cytoplasm, thereby increasing cytoplasmic Zn 2+ concentrations.…”
Section: Zn2+ Homeostasis In Megakaryocytes and Plateletsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Slc39a family was named ZIP (Zrt-, Irt-related protein), after the first two known members Irt1 of Arabidopsis thaliana and Zrt1 of Saccharomyces cerevisiae . So far, the exact structure of mammalian ZIP proteins has not been established, but 14 members of human and mouse ZIP isoforms and their genes have been isolated and characterized [16,17,35]. ZIP family members mediate Zn 2+ influx from the extracellular place into cells, or from the intracellular Zn 2+ store into the cytoplasm, thereby increasing cytoplasmic Zn 2+ concentrations.…”
Section: Zn2+ Homeostasis In Megakaryocytes and Plateletsmentioning
confidence: 99%
“…Several isoforms of ZIP were predominantly expressed, including ZIP1, ZIP4, ZIP6, ZIP7, ZIP9 and ZIP10, while other ZIP isoforms showed limited mRNA expression, and ZIP2 was not detected [26]. Studies in mouse models showed the relevance of ZIP transporters in the regulation of systemic or cellular Zn 2+ homeostasis [16,17,36], but the function of these transporters have been investigated neither in MKs nor in platelets. The members of Slc30a gene family, also called ZnT, are selective Zn 2+ transporters located in the cell surface and on the membrane of intracellular organelles.…”
Section: Zn2+ Homeostasis In Megakaryocytes and Plateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice bran is also rich in potassium, and diets low in potassium have been associated with an increased risk of diabetes in epidemiological studies [ 46 ]. Magnesium, zinc, and calcium supplementation has been shown to improve glycemic control, and cellular pathways involving these minerals have been linked to glucose and insulin homeostasis [ 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes is a progressive and chronic metabolic disease and it is characterized by peripheral insulin resistance and pancreatic beta β cell dysfunction with a growing interest in the role of zinc signaling in this disease [173,189]. GWAS of the past decade have identified variants in the human SLC30A8 gene as affecting the risk of Type 2 Diabetes [189]. Genome-wide association studies demonstrate an association of the above mentioned rs13266634 SNP of ZnT8 with decreased insulin release and T2DM susceptibility [43].…”
Section: Genetic Polymorphisms Involved In Zinc Status and Non Communmentioning
confidence: 99%